Responsividade das células natural killer uterinas DBA+ às alterações nutricionais durante a prenhez de camundongos - Salles, Évila Da Silva Lopes (2014)
Nutritional changes during pregnancy can be harmful to the mother's body and have direct effects in offspring, which can be clarified by uterine components analyses during pregnancy in animal models. Among these components, we can highlight the uterine natural killer cells (uNK), which representing 70% of the lymphocyte population in the murine and humans pregnant uterus. This work aims to evaluate the effects of nutritional changes during mice pregnancy through morphological and behavioral studies. Pregnant mice have received from 1st gestation day (gd) control diet (CD), high- carbohydrate (HC) carbohydrate- 77.7%, high-fat (HF) - 32.5% fat, high-protein (HP) - protein 31.26% and were exposed to food restriction (FR) – 4g CD/day. The animals are killed at 10th gd. Intake, behavior, morphology, cytochemistry, immunocytochemistry, morphometry and stereological Analyzes was undertaken by focusing on uNK. Our data showed that food intake and blood glucose levels of all experimental groups didn’t change, although the weight increased in the HF and decreased in the FR animals. Behavioral analysis in the FR group showed an anxiolytic state, since HF exhibited similar apathy state. Part of the female FR and HC had gestational failure, and implantation sites (SI) resorption were identified in the FR. Analyses by DBA lectin cytochemistry, immunocytochemistry and stereological studies showed HF and HC diets were able to cause marked changes in uNK, decreasing the expression of uNK surface and granules Gal-D-NAc, which enabled the observation of an DBA-lectin altered kind of uterine NK cell (uNKa), with less reactivity to the perforin in their granules. In the endometrium, there was an increased reactivity for Casp-3 and a decreased expression of the α-actin vessels. The changes were less prominent in the uNK from HP and RA animals. HP uNKa were smaller in number than in HF and HC, and had increased morphological senescent uNK subtype, weak casp-3 reaction and strong blood vessels α-actin expression. Similarly to the control animals, in FR, the uNKa were rare, and there was not changes in the perforin or actin vessels expression. However, the FR animals showed a apparently delay in the uNK differentiation as large presence of casp-3. These results showed for the first time different diets could triggering uNK DBA-reactive response as can change mouse uterine microenvironment up to 10th gd.